Bioactive Compounds of Stelechocarpus burahol (Kepel) from Indonesia for Future Perspective of Health: A Literature Review - Zahroh, Endah Wati; Mayasari, Dian; Azzizah, Isma Nur (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Stelechocarpus burahol (Kepel) is widely distributed in Indonesia, where its fruit has traditionally been consumed and used as a natural body fragrance from ancient times to the present. In recent decades, this species has attracted growing interest in the health sector due to its rich content of bioactive compounds. However, the natural population of S. burahol has declined over time and is currently regarded as a conservation species. This article presents an overview of the therapeutic potential of S. burahol and highlights in vitro cultivation strategies aimed at optimizing the production of bioactive metabolites. The review is based on an extensive analysis of scientific journals, conference proceedings, theses, and reference books, using keywords such as S. burahol, Kepel, bioactive compounds, and in vitro culture. Available evidence indicates that S. burahol represents a promising target for bioprospecting in the health sector, particularly due to its reported anti-inflammatory, antioxidant, antibacterial, anticancer, anti-acne, antidiabetic, antihyperuricemic, and anti-implantation activities. Furthermore, in vitro cultivation approaches offer a viable alternative to conventional field cultivation, which remains limited, for the enhanced production of bioactive compounds from this species.